2022
DOI: 10.3389/feart.2022.995874
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the impacts of precipitation phase changes through the hydrologic cycle in snowy regions: From precipitation to reservoir storage

Abstract: Cool season precipitation plays a critical role in regional water resource management in the western United States. Throughout the twenty-first century, regional precipitation will be impacted by rising temperatures and changing circulation patterns. Changes to precipitation magnitude remain challenging to project; however, precipitation phase is largely dependent on temperature, and temperature predictions from global climate models are generally in agreement. To understand the implications of this dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Canada (Han et al, 2018); Tibetan Plateau (Wang et al, 2016); Europe (Blöschl et al, 2019;Matiu et al, 2021;Rixen & Rolando, 2013); and the whole world (Shi & Liu, 2021). Although not examined in this study, a seasonality in precipitation type shift has been reported by Wrzesien et al (2022). Even with warming, winter temperatures are still cold enough the high-latitudes that precipitation will fall mainly as snow, so changes in precipitation type are expected to be more pronounced in fall and spring, explaining why we show increases in both snow days and rain days.…”
Section: More Precipitation Falls As Rain Than As Snow (In Mid-and Hi...mentioning
confidence: 69%
“…Canada (Han et al, 2018); Tibetan Plateau (Wang et al, 2016); Europe (Blöschl et al, 2019;Matiu et al, 2021;Rixen & Rolando, 2013); and the whole world (Shi & Liu, 2021). Although not examined in this study, a seasonality in precipitation type shift has been reported by Wrzesien et al (2022). Even with warming, winter temperatures are still cold enough the high-latitudes that precipitation will fall mainly as snow, so changes in precipitation type are expected to be more pronounced in fall and spring, explaining why we show increases in both snow days and rain days.…”
Section: More Precipitation Falls As Rain Than As Snow (In Mid-and Hi...mentioning
confidence: 69%